Eight new species of Regasilus Curran, 1931 (Diptera: Asilidae: Asilinae) from Peru - Sánchez, Pável (Zootaxa, 2020)
Eight new species in the currently monotypic genus Regasilus Curran, 1931 are described from Peru: Regasilus aiapaec sp. nov. from Piura, R. apu sp. nov. from Cuzco, R. chicamac sp. nov. from Apurímac, Cajamarca, Cuzco, and La Libertad, R. huiracocha sp. nov. from Cuzco, R. illapa sp. nov. from Huancavelica, R. inti sp. nov. from Cuzco, R. supay sp. nov. from Piura, and R. uscovilca sp. nov. from Apurimac and Cuzco. A diagnosis for the genus is given, as well as an identification key to the known species.